(untitled) (Nigerian Journal of Pharmaceutical Research, 2023)
Background: Malaria remains a tropical disease of public health concern. Treating malaria infection without parasitological diagnosis and follow-up yields poor outcomes. Objectives: This study assessed knowledge, attitudes, use of Malaria Rapid Diagnostic Tests (mRDTs), and evaluated impact of a mobile health intervention on case management by community pharmacists. Materials and Methods: The mixed - method study enrolled 112 community pharmacists in Kwara State Nigeria, randomized into control and intervention groups (n = 56 each). Same validated questionnaires were used to obtain baseline and post-intervention data. Only intervention group received educational YouTube videos, mRDT kits and twice-weekly short message service follow-up for six months. Pre- and post- intervention scores were measured and compared in both groups using Mann-Whitney U and t-tests at p <0.05. Results: Baseline knowledge was moderate in both control (5.56 ± 1.41) and intervention (5.70 ± 0.81) groups; significantly improved to high level (8.90 ± 3.20) post-intervention in intervention group (t = 13.07, p = 0.04*) unlike control group (t = 11.25, p = 0.06). Attitude of intervention cohort improved significantly from ‘borderline’ (around 2.5) pre-intervention to ‘positive’ (above 2.5) post- intervention (Z = 3.379, p = 0.001*), unlike control group which remained negative (below 2.5) pre- and post-intervention, (Z = 0.159, p = 0.874). Among controls, mRDT use remained low pre- and post-intervention (6.41 ± 1.21 and 6.65 ± 1.02) (t = 1.1784, p = 0.255); intervention cohort moved from low to moderate (6.58 ± 1.13 to 11.04 ± 1.18) (t = 15.407, p < 0.05*). Conclusion: Both primary (mRDT use) and secondary (knowledge and attitude) outcomes were significantly improved by mHealth intervention. It is recommended that community pharmacists be trained and incentivized to deploy mRDT and digital technologies in routine management of malaria.